Developing Multimedia with STEM Education in University: Needs Analysis in Microbiology Learning - Trio Ageng Prayitno; Nuril Hidayati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
The Microbiology learning at the Department of Biology Education IKIP Budi Utomo not used learning media that integrates digital, technology, and humans to help students understand the concept of microbiology. The purpose of this study was to determine the responses of students and lecturers to multimedia with STEM education (M-STEM) in microbiology learning. The research method is a quantitative descriptive research method through survey techniques with a sample of 43 students and 4 microbiology lecturers at the Department of Biology IKIP Budi Utomo. The research instrument wasa questionnaire consisting of 40 questions for students and 25 questions for lecturers. The results showed that students strongly agreed to use multimedia (62.8%), students were more interested in multimedia (25.6%), students rarely use STEM education (60.5%), students agree that microbiology learning uses the STEM education (58.1%), students are very interested in multimedia with STEM education (90.7%), students agree that multimedia with STEM helps them to understand the concept of microbiology (58.1%), lecturers strongly agree to use the STEM education (100%), and lecturers strongly agree to use multimedia (100%). This study concluded that students and lecturers need M-STEM in microbiology learning at the Department of Biology Education IKIP Budi Utomo.